Book Symposium on "Serbia’s Transition: Towards a Better Future" - Svejnar, Jan; Trumbić, Tea; Woodward, Susan L.; Uvalić, Milica (Taylor and Francis, 2013)
Milica Uvalić has written the first comprehensive book in English on Serbia’s transition. It deals with an important topic and adopts a suitable approach. It includes an ample amount of good data, which, with sharp analysis. The book aims to answer a fundamental question, namely why a country with very good starting conditions has ended up lagging behind.